ANALISIS PERAN SEKTOR PERDAGANGAN DALAM OPTIMALISASI PERTUMBUHAN EKONOMI DI KOTA TERNATE - Novita, Desi; Malau, Albert Gamot (STIE Mahardhika, 2025)
One of the key indicators reflecting the success of economic development in a region is economic growth. The Gross Regional Domestic Product (GRDP) serves as an essential measure for assessing the expansion of regional economies. Through this data, it becomes possible to identify the economic sectors that contribute most significantly to regional growth. The primary objective of this study is to analyze the role of the trade sector and to explore strategies required to enhance its contribution toward optimizing economic growth in Ternate City, North Maluku Province. The study employs secondary data, specifically the GRDP of Ternate City and North Maluku Province for the period 2015–2024. The research methodology incorporates sectoral contribution analysis to GRDP, the Location Quotient (LQ) method, and Klassen typology analysis. The findings reveal that the trade sector constitutes the largest contributor to Ternate City’s GRDP, with an average share of 25.49 percent over the period 2015–2024. Furthermore, the trade sector, identified as one of the base sectors in Ternate City, demonstrates substantial development potential and is classified within Quadrant I (leading sector) of the Klassen typology. In practice, efforts have been undertaken by both the government and society to optimize economic growth in Ternate City.